2022
DOI: 10.1038/s41370-022-00460-7
|View full text |Cite|
|
Sign up to set email alerts
|

A state-of-the-science review and guide for measuring environmental exposure biomarkers in dried blood spots

Abstract: Background Dried blood spot (DBS) sampling is a simple, cost-effective, and minimally invasive alternative to venipuncture for measuring exposure biomarkers in public health and epidemiological research. DBS sampling provides advantages in field-based studies conducted in low-resource settings and in studies involving infants and children. In addition, DBS samples are routinely collected from newborns after birth (i.e., newborn dried blood spots, NDBS), with many states in the United States permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 105 publications
0
19
0
Order By: Relevance
“…Traditional methods of DNA extraction with phenol-chloroform, spin-columns, and magnetic beads can be time-consuming and expensive and need to be performed by trained personnel in a laboratory setting . Dried blood spot (DBS) samples, such as FTA Whatman and plasma separation cards, are newer low-cost alternatives where dried lysis and storage reagents on paper are activated upon sample spotting, thus eliminating the cell lysis step and simplifying sample preparation as well as improving sample storage and transportation for RLS. The cards allow between 40 and 140 μL volume of blood per spot; however, previous reports have shown that volumes of 50–100 μL could lead to inaccurate detection of viral pathogens and so larger sample volumes might be required to ensure optimal performance. Moreover, the uncontrolled flow of blood through the paper can cause the heterogeneous distribution of analytes within the sample spot, leading to variable results obtained from punching different areas of the DBS card. , The NA extraction protocol using these cards requires multiple washing steps to remove inhibitors prior to amplification. , A simpler method involves the addition of prelysed blood to a Whatman No. 1 filter paper disk, which, after a washing step, is added directly to the polymerase chain reaction (PCR) mix for amplification without removing the disk .…”
Section: Microfluidic Devices For Sample Preparation Of Undiluted Who...mentioning
confidence: 99%
“…Traditional methods of DNA extraction with phenol-chloroform, spin-columns, and magnetic beads can be time-consuming and expensive and need to be performed by trained personnel in a laboratory setting . Dried blood spot (DBS) samples, such as FTA Whatman and plasma separation cards, are newer low-cost alternatives where dried lysis and storage reagents on paper are activated upon sample spotting, thus eliminating the cell lysis step and simplifying sample preparation as well as improving sample storage and transportation for RLS. The cards allow between 40 and 140 μL volume of blood per spot; however, previous reports have shown that volumes of 50–100 μL could lead to inaccurate detection of viral pathogens and so larger sample volumes might be required to ensure optimal performance. Moreover, the uncontrolled flow of blood through the paper can cause the heterogeneous distribution of analytes within the sample spot, leading to variable results obtained from punching different areas of the DBS card. , The NA extraction protocol using these cards requires multiple washing steps to remove inhibitors prior to amplification. , A simpler method involves the addition of prelysed blood to a Whatman No. 1 filter paper disk, which, after a washing step, is added directly to the polymerase chain reaction (PCR) mix for amplification without removing the disk .…”
Section: Microfluidic Devices For Sample Preparation Of Undiluted Who...mentioning
confidence: 99%
“…The sample processing involves using a sample collection card and blood lancet. Briefly, after a finger-prick (or prick of the heel in infants) with the lancet, several drops of blood are absorbed onto the sample collection card, followed by drying, storage, shipping, and extraction steps before the analysis [12]. The shipping and storing conditions are simple and might be performed under ambient temperature and humidity in most applications [13].…”
Section: Microsampling Techniques In Therapeutic Drug Monitoringmentioning
confidence: 99%
“…The use of dried blood spot cards is gaining traction as a less invasive means to sample blood with advantages that include smaller sample volume, lower researcher burden (self-collection without the need for a phlebotomist), and lower costs for transport (ambient temperatures) and storage (does not require freezing) [ 135 ]. Blood collected in this way can be used for a wide range of analyses including quantification of nutrients [ 136 ] and application of targeted and untargeted metabolomics [ 137 ] approaches.…”
Section: Translation Of Nutrigenomic Research For Personalised and Pr...mentioning
confidence: 99%